Penerapan Hukuman Mati Tindak Pidana Narkotika Di Indonesia - Lu Sudirman; Elizabeth Gunawan (Journal of Judicial Review, 2015)
This research is to describe about the juridicial policy Application of the death penalty law in Crime Narcotics in Indonesia. This study in terms of laws and regulations related to know what factors are becoming resistor and supporter in applying the death penalty under the provisions of law in Indonesia.This research is a normative research by using the method of qualitative. This type of research is using literature (library search) where is the data collected, the data is then processed and analyzed qualitatively whereby the data obtained and compiled systematically. Furthermore, the conclusions drawn from the results of research and described. The conclusion of this research study is based on the obtained results are reviewed by the author of three problems: first by Law No. 39 Year 1999 concerning the HUMAN RIGHTS according to a human rights perspective on the application of the death penalty in Indonesia. Secondly, based on Law No. 35 Year 2009 on Narcotics namely about how the pros and cons on the basis of the law relating to the death penalty that occurred in Indonesia. Third, in terms of the view of Christianity in comparison with Islam regarding the death penalty in Indonesia.